Bifidobacterium animalis subsp. lactis BB-12 attenuates diabetic retinopathy through gut microbiota modulation: evidence for the gut–retinal axis - Lin, Jiayi; Cheng, Yaqi; Ling, Yumin; Gu, Simin; Zhu, Haocheng; Li, Meng; Yu, Huan; Li, Jianbing; Luo, Qian; Li, Weihua; Ling, Shiqi (Frontiers in Cellular and Infection Microbiology, 2025)
PurposePrevious studies have shown that Bifidobacterium animalis subsp. lactis BB-12 plays a role in maintaining the intestinal barrier and regulating inflammation; however, its potential connection to ocular diseases has not been thoroughly explored. Diabetic retinopathy (DR) is a common ocular complication of diabetes and is closely associated with metabolic dysregulation. This study investigated whether BB-12 supplementation could affect systemic diabetic symptoms, the progression of DR, and the stability of gut microbiota.Materials and methodsDiabetic db/db mice were utilized to monitor metabolic parameters, assess hepatic and lipid profiles, evaluate retinal function via ERG, and examine retinal morphology through OCT and HE staining. Treg/Th17 balance was analyzed by flow cytometry, and gut microbiota composition was profiled using 16S rRNA sequencing.ResultsThe results showed that BB-12 reduced obesity, decreased hepatic steatosis, improved retinal blood vessel health and vision, and influenced both the Treg/Th17 balance and gut dysbiosis in diabetic mice.ConclusionsThese findings lay the groundwork for regulatory role of intestinal microbiota on systemic and ocular complications of diabetes, and further examination of the gut-retina axis.